Life table parameters of the predatory bug Orius laevigatus (Fieber) [Hemiptera: Anthocoridae] preying upon the tobacco whitefly Bemisia tabaci (Gennadius) [Homoptera: Aleyrodidae]. - Abdul-Jalil Hamdan (My University, 2012)
The current study described the life table characteristics of the predatory bug
Orius laevigatus preying upon the tobacco whitefly Bemisia tabaci infestation offered on tomato (Lycopersicon esculentum L. cv 144), and eggplant (Solanum melongena L. cv Classic) leaf discs under laboratory constant conditions of 26±1°C, 75±5% R.H. and 16L:8D photoperiod regime. Average life table parameters for two successive generations of O. laevigatus fed upon Bemisia tabaci infestation offered on tomato and eggplant were calculated respectively according to host plant as: intrinsic rate of increase (Rm): 0.12, 0.038; gross reproductive rate (GRR): 46, 18 insect/female/generation; net reproduction rate (Ro): 20, 2.6 females/female/generation; finite rate of increase (λ): 1.12, 1.038 females/female/day; mean generation time (T): 25.7, 25.2 days; and doubling time (DT): 6, 18.2 days. Those parameters indicated that O. laevigatus has the potential to be used as predator against B. tabaci and that this predator would likely be able to overcome populations of B. tabaci on tomato and eggplant plantation in greenhouses under the conditions similar to those used in this study.
This appears to be the first publication recording the life table parameters of O.laevigatus when used as natural enemy against B. tabaci infestation.

The current study described the life table characteristics of the predatory bug
Orius laevigatus preying upon the tobacco whitefly Bemisia tabaci infestation offered on tomato (Lycopersicon esculentum L. cv 144), and eggplant (Solanum melongena L. cv Classic) leaf discs under laboratory constant conditions of 26±1°C, 75±5% R.H. and 16L:8D photoperiod regime. Average life table parameters for two successive generations of O. laevigatus fed upon Bemisia tabaci infestation offered on tomato and eggplant were calculated respectively according to host plant as: intrinsic rate of increase (Rm): 0.12, 0.038; gross reproductive rate (GRR): 46, 18 insect/female/generation; net reproduction rate (Ro): 20, 2.6 females/female/generation; finite rate of increase (λ): 1.12, 1.038 females/female/day; mean generation time (T): 25.7, 25.2 days; and doubling time (DT): 6, 18.2 days. Those parameters indicated that O. laevigatus has the potential to be used as predator against B. tabaci and that this predator would likely be able to overcome populations of B. tabaci on tomato and eggplant plantation in greenhouses under the conditions similar to those used in this study.
This appears to be the first publication recording the life table parameters of O.laevigatus when used as natural enemy against B. tabaci infestation.
Life table parameters of the predatory bug Orius laevigatus (Fieber) [Hemiptera: Anthocoridae] preying upon the tobacco whitefly Bemisia tabaci (Gennadius) [Homoptera: Aleyrodidae].